Pentagamavunon-1 Enhances the Anticancer Effects of Doxorubicin on Triple-Negative Breast Cancer Cells in Monolayers and 3D Cancer Spheroid Models - Desty Restia Rahmawati; Retno Murwanti; Riris Istighfari Jenie; Arief Nurrochmad (The Indonesian Biomedical Journal, 2025)
BACKGROUND: The 4T1 cells, a triple-negative breast cancer (TNBC) cell line, exhibit high malignancy and metastatic potential. As a primary treatment for TNBC, doxorubicin has limitations, including drug resistance mechanisms and severe side effects such as cardiotoxicity. Pentagamavunone-1 (PGV-1) exhibits antiproliferative and antimetastatic effects, induces prometaphase arrest, triggers cell senescence, and enhances reactive oxygen species (ROS) modulation, which may help overcome doxorubicin resistance. The selective cytotoxicity of PGV-1 against cancer cells suggests that it has a role in reducing systemic toxicity. Therefore, in this study, the anticancer effects of doxorubicin combined with PGV-1 was investigated.METHODS: Monolayer/2D and spheroid/3D models of 4T1 cells were used to assess the effects of PGV-1, doxorubicin, and their combination. MTT assay was used to evaluate the cytotoxicity, colony formation assay was used to measure persistent antiproliferative effects, and spheroid volume analysis was performed to assessed tumor growth inhibition. Senescence-associated beta-galactosidase (SA-β-gal) assay determined cellular senescence.RESULTS: The combination of PGV-1 and doxorubicin significantly enhanced cytotoxicity, with IC50 values of 0.57 µM and 4.88 µM, respectively (p=0.000). A strong synergistic effect was observed, leading to persistent suppression of cancer cell proliferation and an 80% reduction in colony formation (p=0.007). In the 3D spheroid model, combination treatment significantly reduced spheroid volume (p=0.002) more effectively than monotherapy, indicating superior growth inhibition and cytotoxicity. It also increased SA-β-gal, the senescence marker (p=0.010).CONCLUSION: The combination of PGV-1 and doxorubicin demonstrated potent anticancer effects in 4T1 monolayers and spheroid models by enhancing cytotoxicity and inducing cellular senescence. This combination confirmed its potential as a more effective therapeutic strategy.KEYWORDS: 3D spheroid, 4T1 TNBC cell, doxorubicin, pentagamavunon-1, PGV-1, senescence